Experimental and Theoretical Study of the Energy Savings from Wet Ethanol Production and Utilization. Issue 5 (18th March 2014) - López‐Plaza, Emilio Luis; Hernández, Salvador; Barroso‐Muñoz, Fabricio Omar; Segovia‐Hernández, Juan Gabriel; Aceves, Salvador M.; Martínez‐Frías, Joel; Saxena, Samveg; Dibble, Robert
Abstract: As a result of the energy crisis in recent decades, biofuels have gained importance as an option to diminish the oil dependence of automotive industry. Ethanol is one of these biofuels for which demand around the world has increased in recent years. However, to be used as a fuel, the ethanol must be dehydrated to avoid problems in actual engines, and this step has a high energy cost. To overcome this drawback, some studies have demonstrated the use of wet ethanol in homogeneous charge compression ignition (HCCI) engines. In this work, the production of wet ethanol, using conventional distillation, was studied using rigorous simulation studies and experimental tests in a distillation column. The simulation analysis and experimental validation of the energy requirements to obtain wet ethanol were achieved. The results showed that wet ethanol can be produced by using a distillation column with a small number of stages and low reflux ratios, which results in energy savings. Also, the results indicated that for low purities of the distilled ethanol (wet ethanol), the ratios between the energy required during the distillation process and the energy produced by ethanol during the combustion were low. This result implies that the use of wet ethanol can be considered as realistic option in HCCI engines. Abstract : Slippery when wet: The production of high purity ethanol requires high energy consumption for the distillation and dehydration processes (up to 43 % of the lower heating value of the ethanol). As a result, the use of wet ethanol (40 % ethanol‐60 % water by volume mixtures) can increase the net gain of energy. The production of wet ethanol, using conventional distillation, is studied here using rigorous simulation studies and experimental tests in a distillation column.